Preparing medical teachers in their role as mentor for medical students - Shrivastava, Saurabh RamBihariLal; Bobhate, Prateek Sudhakar; Petkar, Prithvi Brahmanand; Mendhe, Harshal Gajanan; Bankar, Nandkishor Jageshwar (Indian Journal of Community Health, 2024)
In conclusion, effective mentoring is a key strategy to support the growth and development of future healthcare professionals. Mentors have a key role to play and we must prepare them for this role so that they prioritize mentorship in their work schedule, and accordingly help students to become competent healthcare professionals.